The Life of Ancient Japan : Selected Contemporary Texts Illustrating Social Life and Ideals before the Era of Seclusion. - Singer, Kurt (Taylor and Francis, 2014)
First Published in 2002. Routledge is an imprint of Taylor & Francis, an informa company.